AKTIVITAS METODE BIMBINGAN PSIKOLOG DAN KONSELOR DALAM MENANGANI PASIEN COVID-19 DI HOSPITAL TENGKU AMPUAN AFZAN KUANTAN PAHANG MALAYSIA - Izzah, Noor; Saragi, Muhammad Putra Dinata (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study aims to offer an overview and understanding of the approaches used by psychologists and counselors to treat COVID-19 infected patients at Tengku Ampuan Afzan Hospital in Kuantan, Pahang, Malaysia, during the pandemic. The technique of data collection approach in this study uses field research methods with qualitative descriptive techniques. Data were obtained through direct observation, interviews with psychologists at Tengku Ampuan Afzan Hospital and documentation. Meanwhile, the content analysis approach was used in the investigation of data analysis. The results obtained from this study are that counseling services at Tengku Ampuan Afzan Hospital Kuantan, Pahang, Malaysia, use technology-based methods to treat COVID-19 patients. Psychologists and counselors in treating covid-19 patients through various online and offline media, such as websites, email, live chat, Skype, Google Meet, Zoom, WhatsApp, and others, to ensure more and efficient access. This approach emerged as a solution to the limited interactions during the pandemic, allowing patients to continue to receive optimal emotional and psychological support. During the pandemic, many psychologists and counselors have come up with new innovations to make service provision more efficient, engaging, and easy, in addition to leveraging technology that is already available.